Penerapan GCG, Audit Internal, Dan Whistleblowing System Sebagai Strategi Pencegahan Fraud Pada PT.XYZ (Persero) - Dina, Nur; Basori, Mohamat; Intan, Lusi Reni; Adiba (CV ODIS, 2025)
This study aims to analyze the influence of the Whistleblowing system and internal audit on fraud occurrences, as well as their roles in supporting Good Corporate Governance (GCG). The analytical method employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), using a sample of 132 employees at PT XYZ (Persero). The findings reveal that both the Whistleblowing system and internal audit have a positive and significant effect on GCG but do not have a significant impact on fraud occurrences. Furthermore, GCG itself is not proven to significantly reduce the incidence of fraud. These results imply that improvements in internal control and reporting systems should be accompanied by additional efforts to effectively mitigate fraud within the organization.